2002
DOI: 10.2754/avb200271030341
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Products of Nitric Oxide and the Concentrations of Antioxidant Vitamins in Parasitized Goats

Abstract: The status of nitric oxide oxidation products and antioxidant vitamins were investigated in goats infected with endoparasites and blood parasites (Trichostrongylidae sp. + Protostrongylidae sp. + Eimeria sp. + Babesia sp.), in this study. Eighteen goats were naturally infected with these parasites and ten healthy goats served as controls which had been treated with antiparasitic drugs after parasitological examinations were carried out. The concentrations of nitric oxide oxidation products (nitrate, nitrite) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Lipid peroxidation may also be intensified because of decreasing vitamin E levels in the course of infection with F. hepatica. Reductions in vitamin E content of the host were observed in other parasitic diseases as well (Sarin et al 1993;Dede et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…Lipid peroxidation may also be intensified because of decreasing vitamin E levels in the course of infection with F. hepatica. Reductions in vitamin E content of the host were observed in other parasitic diseases as well (Sarin et al 1993;Dede et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, no statistical difference was evident in the concentrations of the antioxidant vitamins (A, E and C) between the healthy and diseased sheep. Although there are no documented reports on the status of antioxidant vitamins in malignant ovine theileriosis, some studies on other hemoparasitic diseases (such as babesiosis) showed decreased serum levels of such vitamins in infected animals and this phenomenon may be a consequence of oxidative damage (Deger et al, 2009;Bicek et al, 2005;Dede et al, 2002). It can be proposed that despite being evident that antioxidant systems comprised of vitamins have a cellular protective action against oxidative stress (Dede et al, 2000), the unchanged level of antioxidant vitamins in our work may be attributed to the occurrence of an equilibrium between the level of vitamin uptake in the diet and the level in the serum and body tissues, particularly the liver storage.…”
Section: Discussionmentioning
confidence: 99%
“…When the cellular oxidant state is overwhelmed by excess production of reactive oxygen species (ROS), cellular damage occurs through oxidative stress and lipid peroxidation (LPO) (Saleh et al 2011). Alteration of oxidative stress indices have been reported in parasitic diseases (Dede et al 2002;Pabon et al 2003). LPO is one of the ideal parameters of oxidative stress and malondialdehyde (MDA); an LPO product is used as a biomarker for free radical-mediated damage (Kuhn and Borchert 2002).…”
Section: Introductionmentioning
confidence: 99%